Effectiveness Economic Welfare Through Bansos During Covid-19 in Payakumbuh City - Sufiawan, Nur Ari; Iryani, Nelvia (JEJAK: Jurnal Ekonomi dan Kebijakan, 2021)
The purpose of this study was to determine the effectiveness of mitigating the economic vulnerability of the community through the allocation of social assistance during the Covid-19 pandemic in Payakumbuh City. The data used are primary data and secondary data. Collecting data in the form of observation, documentation and interviews with a sample size of 100 respondents. The analytical method used is descriptive qualitative. The results of the analysis show 1) the input aspect with an effectiveness ratio of 60% and 65% can be said to be quite effective, meaning that KPM is right on target and utilizes social assistance appropriately for the economic benefit of the community in the midst of the Covid-19 outbreak. 2)which consists of socialization and monitoring, each with an effectiveness ratio of 100%. 3) the output aspect of social welfare with an indicator of the level of fulfillment of needs where the percentage obtained is 74% in the category of economic welfare which is quite effective.